Initial studies of the structural signal for extracellular transport of cholera toxin and other proteins recognized by Vibrio cholerae. - Connell, T D (1995)
The specificity of the pathway used by Vibrio cholerae for extracellular transport of cholera toxin (CT) and other proteins was examined in several different ways. First, V. cholerae was tested for the ability to secrete the B polypeptides of the type II heat-labile enterotoxins of Escherichia coli. Genes encoding the B polypeptide of LT-IIb in pBluescriptKS- phagemids were introduced into V. cholerae by electroporation. Culture supernatants and periplasmic extracts were collected from cultures of the V. cholerae transformants, and the enterotoxin B subunits were measured by an enzyme-linked immunosorbent assay. Results confirmed that the B polypeptides of both LT-IIa and LT-IIb were secreted by V. cholerae with efficiencies comparable to that measured for secretion of CT. Second, the plasmid clones were introduced into strain M14, an epsE mutant of V. cholerae. M14 failed to transport the B polypeptides of LT-IIa and LT-IIb to the extracellular medium, demonstrating that secretion of type II enterotoxins by V. cholerae proceeds by the same pathway used for extracellular transport of CT. These data suggest that an extracellular transport signal recognized by the secretory machinery of V. cholerae is present in LT-IIa and LT-IIb. Furthermore, since the B polypeptide of CT has little, if any, primary amino acid sequence homology with the B polypeptide of LT-IIa or LT-IIb, the transport signal is likely to be a conformation-dependent motif. Third, a mutant of the B subunit of CT (CT-B) with lysine substituted for glutamate at amino acid position 11 was shown to be secreted poorly by V. cholerae, although it exhibited immunoreactivity and ganglioside GM1-binding activity comparable to that of wild-type CT-B. These findings suggest that Glu-11 may be within or near the extracellular transport motif of CT-B. Finally, the genetic lesion in the epsE allele of V. cholerae M14 was determined by nucleotide sequence analysis.